THE EFFECTIVENESS OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION IN MECHANICAL NECK PAIN: A SYSTEMATIC REVIEW - Made Hendra Satria Nugraha; Anak Agung Gede Angga Puspa Negara; Ni Komang Ayu Juni Antari; Anak Ayu Nyoman Trisna Narta Dewi (Sport and Fitness Journal, 2021)
Introduction: Neck pain is a health condition that has a high incidence rate and causes an inability to do daily activities and requires cost in handling it. People with neck pain could be associated with an alteration and deficit of the proprioception of the muscle and neck joint that play a significant role in joint position, postural stability, and motor control of the head and neck. Objective: The purpose of this systematic review is to find out the effectiveness of proprioceptive neuromuscular facilitation in mechanical neck pain. Method: The systematic review access to journal databases such as: PubMed Central (PMC) NCBI, Physiotherapy Evidence Database (PEDro), ProQuest, Google Scholar, MEDLINE, and the Cochrane Controlled Trials Register in the Cochrane Library. Results: The initial search in 6 databases found a total of 30 articles. Based on inclusion and exclusion criteria 4 articles were used in this systematic review. The application of the muscle energy techniques was applied ranging from 1 time to 8 weeks of intervention. From the 4 reviewed studies concluded that proprioceptive neuromuscular facilitation was effective in improving neck range of motion and function in mechanical neck pain. Conclusion: Based on the results of this systematic review it can be concluded that proprioceptive neuromuscular facilitation is effective in improving pain, pain threshold, range of motion, and functional performance in individual with neck pain. The appropriate articles are still limited to 4 studies, but have good to strong qualities. In addition, the application of intervention does not have the same standard.